Persepsi Masyarakat Tentang Keberadaan Monyet Ekor Panjang (Macaca Fascicularis) di Desa Tumbang Nusa Kabupaten Pulang Pisau Kalimantan Tengah - Ise Afitah (Anterior Jurnal, 2016)
This study aims to determine the perception that people living around the forest areas in conserving forest habitat preservation especially of the long tail monkey (Macaca fascicularis). Communities around the region are not yet aware of the importance of wildlife reserves mainly habitat the long tail monkey (Macaca fascicularis). Local communities know of the existence of the long tail monkey (Macaca fascicularis) in their area which is about 84.3% and most of them know by direct presence of the long tail monkey (Macaca fascicularis) in the amount of 67.1% but the local people do not know about nature conservation and habitat the long tail monkey ie 71.4% and most of them without intentional conduct habitat destruction and very little involved in conservation of the long tail monkey, including the open field activity of 60%, logging 52.9% and it does not matter to extinguish the flames during a wildfire that is 82.9%. It needs a continuous program and continuous from the relevant stakeholders to provide socialization to the local communities so that people can know about the conservation of nature and habitat of the long tail monkey, in the short term is necessary to rescue of the long tail monkey habitat that has been there from further damage.